2020
DOI: 10.1128/aac.02001-20
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated Nanomaterials with Broad-Spectrum Antiviral Activity Extending beyond Heparan Sulfate-Dependent Viruses

Abstract: Viral infections are among the main causes of death worldwide and we lack antivirals for the majority of viruses. Heparin-like sulfated or sulfonated compounds have been known for decades for their ability to prevent the infection of heparan sulfate proteoglycans (HSPG) dependent viruses, even though only in a reversible way. We have previously shown that gold nanoparticles and β-cyclodextrins coated with mercapto-undecane sulfonic acid (MUS) inhibit HSPG-dependent viruses irreversibly, while retaining the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…This mechanism may then not be applicable to CoVs due to the distance between the RBD and the envelope. Alternatively, and as previously described for VSV [32], the absence of virucidal activity of MUS:OT NP and MUS CD could be due to the poor affinity of the SARS-CoV-2 spike protein for HS. This second scenario is supported by the absence of inhibitory activity of heparin and other sulfated compounds in our experimental settings.…”
Section: Discussionmentioning
confidence: 69%
“…This mechanism may then not be applicable to CoVs due to the distance between the RBD and the envelope. Alternatively, and as previously described for VSV [32], the absence of virucidal activity of MUS:OT NP and MUS CD could be due to the poor affinity of the SARS-CoV-2 spike protein for HS. This second scenario is supported by the absence of inhibitory activity of heparin and other sulfated compounds in our experimental settings.…”
Section: Discussionmentioning
confidence: 69%
“…[117] Therefore, a more complex architecture was designed as an alternative to PRO2000, a 16 kDa dendrimer functionalized with sodium 1-(carboxymethoxy) naphthalene 3,6-disulfonate labeled as SPL7013 (Figure 7A). SPL7013 inhibited HIV-1, HSV-1, and Huskens et al [ 114] Keller et al [ 115,117] Pirrone et al [ 116] SPL7013 (VivaGel) M n = 16 kDa See Figure 7A Rupp et al [ 118] Dezzutti et al [ 119] McGowan et al [ 120] Price et al [ 121] Carboxylate/phosphonate/sulfonate RAFT polymers M n from 1.8 to 84.7 kDa Schandock et al [ 123] Polyacrylamides containing benzoboroxole moieties obtained by free radical polymerization M n = 100 kDa Mahalingam et al [ 124] MUS-functionalized gold NPs ≈2.5 nm Cagno et al [ 5,125] HSV-2 infections in vitro and in animal models, even when administered post-infection. [118,119] There is evidence that the dendrimer inhibits both viral entry and replication, thus acting at different stages of infection.…”
Section: Sulfated/sulfonated Non-glycosylated Polymersmentioning
confidence: 99%
“…Interestingly, additional studies demonstrated that the MUS-functionalized NPs were virucidal against influenza A (H1N1), though its mechanism for viral entry was independent of HSPGs and was instead enabled by the binding of viral particles to the sialic acid groups presented at the surface of host cells. [5] This activity was partly attributed to the affinity of influenza hemagglutinin protein to sulfate or sulfonate moieties, but also to the long alkyl spacer of MUS being an essential attribute for the inactivation of viral particles, as heparin was only weakly virustatic against H1N1. As promising in vivo efficacy was reported with MUS-functionalized NPs for the treatment of RSVinfected mice, further analyses on a wider range of viral strains were recommended.…”
Section: Sulfated/sulfonated Non-glycosylated Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold nanoparticles coated with sulfonic acid inhibit different strains of influenza virus that do not bind HSPGs. The antiviral action is virucidal and irreversible for influenza A (H1N1, H3N2, and H5N1) and B virus strains (2).…”
Section: Introductionmentioning
confidence: 99%